Membangun Human Capital Melalui Kepemimpinan Dan Komitmen Organisasi - Nasih, Moh (UNIVERSITAS NEGERI SURABAYA, 2011)
AbstractEvery company is constructed through two kinds of capital, which is financial capital and intellectual capital. If the company's capital is described as a tree, the human capital, an essential part of intellectual capital, is the resin. Resin allows the tree grows, and only the human capital that enables organizations to grow and develop. Considering the strategic position of human capital, it is a compulsion for a company to develop it. The problem is how to build human capital effectively? This study aimed to identify the factors that determine the development of human capital in an organization. There are 2 (two) major factors that hypothetically influence human capital, which is leadership and organizational commitment. Leadership does not directly affect human capital. Leadership influence human capital through organizational commitment. In other words, organizational commitment is an intervening variable for the relationship or the influence of leadership on human capital. This hypothesis is based on a 'fact' that the function of leadership is oriented and intended to obtain or build the commitment of each personnel. Only committed personnel will provide their best for the organization. Only through the best contributions of every personnel, human capital can be built and developed. Leadership is useless if it can not obtain and create commitment. Personnel are useless, no matter how many and how skilfull they are, if they do not contribute the best for the organization. The presence of personnel without their comitment will be the same with their absence; even they may actually be detrimental to the organization.